Dielectric and thermal studies of the segmental dynamics of poly(methyl methacrylate)/silica nanocomposites prepared by the sol–gel method. Issue 6 (10th October 2012) - Kyriakos, Konstantinos; Raftopoulos, Konstantinos N.; Pissis, Polycarpos; Kyritsis, Apostolos; Näther, Franziskus; Häußler, Liane; Fischer, Dieter; Vyalikh, Anastasia; Scheler, Ulrich; Reuter, Uta; Pospiech, Doris
Abstract Poly(methyl methacrylate)/silica (PMMA/SiOx) nanocomposites were synthesized via sol–gel method and studied by various techniques. The dispersion of the silica particles (10–100 nm) in the matrix was probed by transmission electron microscopy (TEM), while solid‐state NMR and Raman spectroscopy detected the formation of an inorganic network with high degree of crosslinking. To elucidate the impact of the filler on the molecular dynamics of the PMMA, different methods were used; namely differential scanning calorimetry, thermally stimulated depolarization current and broadband dielectric relaxation spectroscopy. All three methods observed a significant impact of the nanoparticles on the segmental dynamics of the matrix, which was expressed as an increase of the glass transition temperature (Tg) in terms of calorimetry and as a shift of the α (segmental) relaxation to lower frequencies in terms of dielectric spectroscopy. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013